IMPLEMENTASI PASAL 24 CONVENTION ON THE RIGHTS OF PERSONS WITH DISABILITIES (CRPD) TENTANG PENDIDIKAN INKLUSIF DI SEKOLAH LUAR BIASA SRI MUJINAB PEKANBARU TAHUN 2013-2016 - Tegar Christopher Yolanda; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The This study analyzes on how implementation article 24 Convention on The rights of persons with disability about education in SLB Sri Mujinab Pekanbaru. Indonesia has ratified several international conventions as protective measures against human rights for persons with Disability, including the Convention on the rights of persons with disability. In addition, the Government of Indonesia also have formed numerous attempts of protection of human rights and justice for people with Disability, but in fact in Indonesia are still going on against the violations of human rights for persons with Disability, particularly in the field of education.The methods that is used by the writer is the qualitative research. Qualitative research isintends to look at the process of the implementation of article 24 of the CRPD at SLB Sri Mujinab Pekanbaru. Research materials is based on secondary data through the study of literature such as books, internet, and more.The end result of this research is that the implementation of article 24 the CRPD in SLB Sri Mujinab Pekanbaru is very good because it meets the characteristics of education for inclusive and meet the inclusive school characteristics. Moreover, it can also be seen First, implementation of article 24 of the CRPD in Sri Mujinab Pekanbaru,can be implemented, it can be seen from the existence of the facilities and infrastructure that supports the realization of the rights of persons with disability in terms of education, one of the goals of this country become independent is to the intellectual life of the nation, education is a human right, as well as the constitutional rights of citizens which was carried out by the State. Second, the Government's role in removing discrimination for persons with disability was ratified the Convention on The Rights of Persons with Disabilities (CRPD), as a foundation of the State in ensuring the protection of human rights and fundamental freedoms of persons with disability without discrimination.Key words : CRPD,Human Rights,SLB Sri Mujinab Pekanbaru,Inclusive Education